A revision of the African hygropetric genus Coelometopon Janssens, and description of Oomtelecopon new genus (Coleoptera: Hydraenidae) - Perkins, Philip D. (Zootaxa, 2005)
The African hygropetric beetle genus Coelometopon Janssens is revised, and Oomtelecopon new genus is described, based on the study of 1,884 specimens. The genus Coelometopon is redescribed, and redescriptions are provided for C. cavifrons Janssens, C. leleupi Janssens, C. madidum Janssens, and C. mussardi Janssens. Eighteen new species of Coelometopon and two new species of Oomtelecopon are described. The two genera are placed in the Coelometoponini, new tribe, of the subfamily Prosthetopinae. A key to the two genera and 24 known species is given. High resolution digital images of all holotypes are presented (online version in color), the male genitalia are illustrated, and geographic distributions are mapped. Structural details of a representative species, C. granulatum, are illustrated with scanning electron micrographs. Members of Coelometopon are restricted to hygropetric microhabitats, being found on vertical or near vertical rock surfaces which have a thin film of flowing water, such as rock seeps and splash zones of waterfalls and cascades. Members of Oomtelecopon have been collected from algae in seeps, from wet cliff faces, and by sifting marsh shore litter. New species of Coelometopon are: C. angulatum (Lesotho: Mamathes, 5 mi. E. Tayateyaneng), C. balfourbrownei (South Africa: Cape Prov., George District, near George), C. blinkwater (South Africa: Cape Prov., Table Mountain, Blinkwater ravine), C. brincki (Lesotho: Mamathes, 5 mi. E. Tayateyaneng), C. clandestinum (South Africa: Natal Prov., Olivershoek Pass), C. coronatum (Lesotho: Mamathes, 5 mi. E. Tayateyaneng), C. costatum (South Africa: Transvaal Prov., Zoutpansberg, 6 mi. NNE Louis Trichardt), C. drakensbergense (South Africa: Natal Prov., Drakensburg, Cathedral Peak, Mikes Pass), C. emarginatum (South Africa: Transvaal Prov., Nelshoogte, Knuckles rocks forest), C. endroedyi (South Africa: Natal Prov., Drakensburg, Loteni Reserve), C. fimbriatum (South Africa: Cape Prov., Swellendam District, Langeberge Mountains, Tradouw Pass), C. granulatum (South Africa: Natal Prov., Mpumalanga, 13 km E Sabie), C. kilimanjaro (Tanzania: Kilimanjaro, Marangu), C. langebergense (South Africa: Cape Prov., Swellendam District, Langeberge Mountains, Tradouw Pass), C. minipunctum (South Africa: Natal Prov., Drakensberg, Cathedral Peak, Rainbow G.), C. natalensis (South Africa: Natal Prov., Mpumalanga, 28 km N Graskop), C. punctipennis (South Africa: Cape Prov., Xalanga District, Cala Pass), and C. zulu (South Africa: Natal Prov., Zulu Drakensberg, 7 km N Nogome Forest Reserve). New species of Oomtelecopon are: O. sebastiani (South Africa: Cape Prov., Cape-Cederberg), and O. setosum (type species) (South Africa: Cape Prov., Table Mountain, Blinkwater Ravine).